Cultural condition improvement for xylanase production by Bacillus subtilis GN156 - Kuancha, Chutuna; Apiraksakorn, Jirawan (Asia-Pacific Journal of Science and Technology, 2017)
Xylanase is important enzyme widely used in industrial process for xylose, xylitol, and xylooligosaccharides production, which is multipurpose used in food and pharmaceutical industries. To increase the production of xylanase from Bacillus subtilis GN156, the physical parameters were focused. By varying temperature (25, 30 and 40 °C), shaking speed of the incubator shaker (150 and 200 rmp) and pH of culture medium (4-8), the optimum condition for xylanase fermentation was found at pH 7, 30ºC and 200 rpm. The maximum xylanase was 1.86 folds higher than those from the production at the non-optimization condition at 37°C, 200 rpm and without pH control. Therefore, temperature, pH and speed of the incubator shaker were the affecting factors to xylanase production by B. subtilis GN156.